If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -8 + 5 = 0 Reorder the terms: -8 + 5 + 6y = 0 Combine like terms: -8 + 5 = -3 -3 + 6y = 0 Solving -3 + 6y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 6y = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 6y = 0 + 3 6y = 0 + 3 Combine like terms: 0 + 3 = 3 6y = 3 Divide each side by '6'. y = 0.5 Simplifying y = 0.5
| 0.5q-4=5 | | 45-(3x-.56)= | | 0.15x+0.05(4-x)=0.10(16) | | -7(6+3n)=-16+5n | | 32-4x=-5(4x+5)-5(-8-3x) | | 40X+50=Y | | 4x^2+x-4=1 | | -5b+9=71 | | b-8=-12 | | (9r^4-37r^2).25r= | | 0.4m-0.7=22 | | 3(2p+6)-4(p-8)= | | n*1=5 | | 0.14y+0.09(y+5000)=2520 | | 9x-(8x+6)=3x-40 | | 17-3k=8k+7(6+2k) | | 20x+16=25 | | -115b+80=-489 | | 5m+(m+1)=23 | | 8n-3(n-1)=-5+33 | | 3(h-2)=18 | | g^3(3g^3-13)= | | -115b+80=-89 | | -115b+80=-49 | | -x-8=4 | | 4(3x-2)-5x=6-(2x-1) | | 3(x-2)=-36-7x | | .5b+4=2+3d-.5 | | 2x+10=x-6 | | -97=6(3n-2)-n | | 2p-2(6-2p)=2(p-5)-2 | | -3n-16=7(n+2) |